2015
DOI: 10.1039/c5cc05848a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation and amplification of an enantioenriched α-amino nitrile: a chiral precursor for Strecker amino acid synthesis

Abstract: Without the addition of any chiral substances, the spontaneous formation of an enantioenriched α-amino nitrile (up to 96% ee), which is a chiral precursor for Strecker amino acid synthesis, has been achieved in combination with conglomerate formation. The frequency of the formation of enantiomorphs exhibits an approximate stochastic distribution, i.e., L-form occurred 21 times and D-form occurred 22 times, which fulfils the conditions necessary for spontaneous absolute asymmetric synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 63 publications
(12 reference statements)
0
42
0
Order By: Relevance
“…The Strecker reaction between achiral 1 , o ‐tolualdehyde ( 3 c ), and HCN was conducted in 1.5 m solution of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) in methanol (Figure a and the Supporting Information Table S2). As the three‐component reaction proceeded, solid 4 c appeared spontaneously in enantioenriched form; thus, total spontaneous resolution occurred as observed in the formation of 4 b . To check the distribution of the molecular handedness and the ee , further Strecker reactions were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Strecker reaction between achiral 1 , o ‐tolualdehyde ( 3 c ), and HCN was conducted in 1.5 m solution of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) in methanol (Figure a and the Supporting Information Table S2). As the three‐component reaction proceeded, solid 4 c appeared spontaneously in enantioenriched form; thus, total spontaneous resolution occurred as observed in the formation of 4 b . To check the distribution of the molecular handedness and the ee , further Strecker reactions were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported on the spontaneous formation (total spontaneous resolution) of enantioenriched α‐aminonitrile 4 b (see Figure in Table for the chemical structure) in combination with the Strecker reaction between three achiral substrates . The tiny imbalance of the enantiomorphous aminonitriles could be greatly amplified from ca.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Since its discovery in 2005, severalc onditions and parameters weres creened to improve the efficiency of this technique. [1,[8][9][10] Organic compounds, such as amino acids and their derivatives, [11,12] organometallic complexes [13] and pharmaceutical intermediates, [4,5] were successfully deracemized by using Viedma ripening. Duringt he process, as lurry of the conglomerate crystalsi nas aturated solution is intensively ground to promote breakage and dissolution as well as growth of the crystals.…”
Section: Introductionmentioning
confidence: 99%
“…30 Furthermore, Kawasaki and co-workers have shown how amino nitriles can be synthesized from Strecker reactions and obtained in high ees through crystallization or attack of HCN to a specific imine crystal face. 37,38 We were delighted to find that using 20 mol% of amino nitrile, as before, gave 2-deoxy-D-ribose in similar yields and selectivities to those achieved with the amino ester promoters (compare entries 3 and 9, or 6 and 12). Importantly, we also found that after 24 hours in an aqueous environment there was no observed erosion of the %ee of L-valine nitrile via polarimetry studies.…”
mentioning
confidence: 99%